IMPLEMENTASI STRUKTUR DATA TREE PADA WEB BLOG SEBAGAI MEDIA PEMBELAJARAN - Serly Agustin; Arifin Yusuf Permana; Hari Noer Fazri; M. Rahssyal Daffa H; Mohammad Robi; Ricky Firmansyah (Pusat Riset dan Inovasi Nasional, 2022)
In writing this study aims to review the implementation of tree data structures on web blogs as learning media, starting from a discussion of the implementation of data structures. After that, it was continued with the use of blogs as an applied learning medium. The use of tree data structures is one of the most common data structures used in the development of a web. One of the efforts to streamline and provide a variation in the realm of learning media is to create a web blog, especially in the era of globalization, everyone who lives in that era should at least know about one of the results of technological and communication advances. This study will see how the description or description of the application of tree data structures on blogs as learning media. The making of this research uses a qualitative descriptive method in which the data is obtained from observation and documentation of matters relating to the topic under study. The core discussion of this research is the implementation of data structures on blogs as learning media.